2023
DOI: 10.4012/dmj.2022-096
|View full text |Cite
|
Sign up to set email alerts
|

Metal-organic framework-based nanoplatform enhance fibroblast activity to treat periodontitis

Abstract: After periodontal tissue injury, reconstruct soft tissue sealing around the tooth surface is of fundamental importance to treat periodontitis. Among multiple cell types, fibroblast plays a central role in reestablishing functional periodontium. To enhance fibroblast activity, a novel metal-organic framework-based nanoplatform is fabricated using mesoporous Prussian blue (MPB) nanoparticles to load baicalein (BA), named MPB-BA. Drug release test displayed sustained BA release of MPB-BA. Cell proliferation, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Jiao and colleagues successfully loaded baicalein onto HPBNZs and demonstrated that this drug-loaded HPBNZ formulation promoted fibroblast proliferation and accelerated wound healing. 63…”
Section: The Versatile Applications Of Pbnzs As Therapeutic Agents In...mentioning
confidence: 99%
“…Jiao and colleagues successfully loaded baicalein onto HPBNZs and demonstrated that this drug-loaded HPBNZ formulation promoted fibroblast proliferation and accelerated wound healing. 63…”
Section: The Versatile Applications Of Pbnzs As Therapeutic Agents In...mentioning
confidence: 99%